FEEDING EFFECT OF SOYBEAN MEAL TANNINS PROTECTED AGAINST NITROGEN BALANCE OF THIN TAILED SHEEP - Husnaeni Husnaeni (UNIVERSITAS SEMBILANBELAS NOVEMBER KOLAKA, 2016)
The study was aimed to determine the effect of granting Soybean meal protection against nitrogen balance of thin tailed sheep (male). The experimental animals were 16 thin tailed sheeps (males) aged 8 months old with average body weight of 11.81 ± 1.65 kg. The research was assigned in completely randomized design (CRD) 4 treatments and 4 replicates T0 (complete feed + soybean meal without tannins), T1 (complete feed + protected soybean meal 0.5% tannins), T2 (complete feed + protected soybean meal 1% tannin), and T3 (complete feed + protected soybean meal 1.5% tannins). The parameters observed dry matter intake (DMI), DMI /% BB, DMI / BB0.75, nitrogen intake (NI), N-Faecal, N-Urine, N-Digested and N-Retention. Data were variance analyzed by F test (P0.05), followed by Duncan's Multiple Range Test. The results showed that DMI, DMI /% BB, DMI / BB0.75, nitrogen intake (NI), N-Faecal and N-Digested no effect (P0,05) of treatment. N-Retention Lowest in T2 (9,87 g/day) while T0 (11,76 g/day), T1 (11,71 g/day), T3(11,86 g/day) no significant (P0,05), inversely with N-Urine decreased in T2 (3,09 g/day) dan T0 (2,04g/day), T1 (2,23 g/day) dan T3 (1,95 g/day) no significant (P0,05) as a result of treatment. Based on the results of this study concluded that the use of various mangrove leaf tannin levels up to 1.5% to protect soybean meal no effect on consumption, N-Faecal, and N-digested but protection cake with tannin 1% decrease N-retention and increase the excretion of N-Urine.